TEACHING READING COMPREHENSION BY USING 3H (HERE, HIDDEN, IN THE HEAD )STRATEGY TO THE EIGHTH GRADE STUDENTS OF SMP NEGERI O MANGUNHARJO - agus triyogo (Journal of English Education, Literature and Linguistics, 2018)
The main problem of this study was “Is it effective to teach reading comprehension by using 3H strategy to the eighth grade students of SMP Negeri O Mangunharjo in the academic year of 2016/2017?”. Therefore the objective of this study was to find out whether or not it is effective to teach reading comprehension by using 3H strategy to the eighth grade students of SMP Negeri O Mangunharjo in the academic year of 2016/2017. There were two hypotheses in this research, the null hypothesis (Ho) which stated that it is not effective to teach reading comprehension by using 3H strategy to the eighth grade students of SMP Negeri O Mangunharjo in the academic year 2016/2017 and the alternative hypothesis (Ha) stated that it is effective to teach reading comprehension by using 3H strategy to the eighth grade students of SMP Negeri O Mangunharjo in the academic year 2016/2017. There were 31 students treated as the sample of the study taken from eighth grade classes as the population of this investigation. The sample was taken by using cluster random sampling. The pre experimental method was applied in this study. The data were collected by written test in multiple choice form. The data from the test were analyzed through individual score, minimum mastery criteria, and matched t-test. From the data analysis, the writer found out that it was different between the students score before and after the treatment. Moreover, the result of matched t-test calculation was higher than the coefficient of the t-table. The result of matched t-test calculation shows that the tobt was 17.78, whereas, the coefficient critical value of t-table was 1.697 for significant level 0.05 for df 30. So, the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. So, it was effective to teach reading comprehension by using 3H strategy to the eighth grade students of SMP Negeri O Mangunharjo in the academic year of 2016/2017.